2012
DOI: 10.1093/nar/gks287
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide profiles of H2AX and γ-H2AX differentiate endogenous and exogenous DNA damage hotspots in human cells

Abstract: Phosphorylation of the histone variant H2AX forms γ-H2AX that marks DNA double-strand break (DSB). Here, we generated the sequencing-based maps of H2AX and γ-H2AX positioning in resting and proliferating cells before and after ionizing irradiation. Genome-wide locations of possible endogenous and exogenous DSBs were identified based on γ-H2AX distribution in dividing cancer cells without irradiation and that in resting cells upon irradiation, respectively. γ-H2AX-enriched regions of endogenous origin in replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(94 citation statements)
references
References 25 publications
5
89
0
Order By: Relevance
“…after irradiation), is however also accumulated on chromatin under replicative stress. Therefore, γH2AX may be used as a marker of replicative stress in rapidly dividing cells, such as cancer cells (Seo et al, 2012;Ward and Chen, 2001). In untreated E6.5 embryos we detected endogenous γH2AX both in the Epi and in the ExE, suggesting that these tissues are dealing with replicative stress (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…after irradiation), is however also accumulated on chromatin under replicative stress. Therefore, γH2AX may be used as a marker of replicative stress in rapidly dividing cells, such as cancer cells (Seo et al, 2012;Ward and Chen, 2001). In untreated E6.5 embryos we detected endogenous γH2AX both in the Epi and in the ExE, suggesting that these tissues are dealing with replicative stress (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…The loss of accessibility is accompanied by a gain of H3, indicating that the progressively occurring chromatin compaction is achieved either by active chromatin remodeling or incorporation of new nucleosomes. Although previous studies have suggested that heterochromatic regions are less prone to DNA damage in response to ionizing irradiation, γ-rays or chemical agents (Falk et al, 2008;Seo et al, 2012;Takata et al, 2013; Wei Yu, Genome-wide analysis of DNA damage and repair, Technische Universität Darmstadt, PhD thesis, 2014), our and other published data indicate that UV-induced DNA damage might occur both in eu-and hetero-chromatic regions (Wei Yu, Genome-wide analysis of DNA damage and repair, Technische Universität Darmstadt, PhD thesis, 2014; Zavala et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide mapping of H2A.X in resting T-cells indicated that the variant was relatively randomly distributed throughout the genome (Seo et al, 2012).…”
Section: H2axmentioning
confidence: 99%